2018
DOI: 10.1108/ecam-10-2017-0219
|View full text |Cite
|
Sign up to set email alerts
|

Phase-based analysis of key cost and schedule performance causes and preventive strategies

Abstract: Purpose It is estimated that more than half of the construction industry’s projects encounter significant cost overruns and major delays, resulting in the industry having a tarnished reputation. Therefore, it is crucial to identify key project cost and schedule performance factors. However, despite the attempts of numerous researchers, their results have been inconsistent. Most of the literature has focused solely on the construction phase budget and time overruns; the engineering/design and procurement phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…In 1987 [28], Pinto and Slevin espoused that a project can be considered successful if it is completed on time, on budget, meets all its objectives, and satisfies the client. Various studies have been conducted on successful construction projects, using their definition [29,30,31,32,33,34,35]. Almost all researchers believe that staying within the budget, adhering to the schedule, and achieving a quality project performance, referred to as "the iron triangle" by Atkinson [36] is necessary for the success of a construction project [37,38,39,40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 1987 [28], Pinto and Slevin espoused that a project can be considered successful if it is completed on time, on budget, meets all its objectives, and satisfies the client. Various studies have been conducted on successful construction projects, using their definition [29,30,31,32,33,34,35]. Almost all researchers believe that staying within the budget, adhering to the schedule, and achieving a quality project performance, referred to as "the iron triangle" by Atkinson [36] is necessary for the success of a construction project [37,38,39,40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These changes in construction projects are almost inevitable, and they usually bring excessive claims, disputes, additional work, and duplication of efforts contributing a project to experience a delay [30,31]. Similarly, Habibi & Kermanshachi [32] concluded that design changes are often responsible for deferring time completion and adding cost in both the engineering and construction phases [33]. Not only can any modifications be attributed to the design changes, but also any additions or deletions to the scope of the work can change the agreed framework in the contract.…”
Section: Factors Affecting Epc Project Performancementioning
confidence: 99%
“…The construction industry has been considered a key contributor to economic growth in many nations, playing a significant role in sustainable development (Ofori, 2015; Oesterreich and Teuteberg, 2016; Habibi and Kermanshachi, 2018). The adoption of new technological advancements in this industry is a path toward achieving project success.…”
Section: Introductionmentioning
confidence: 99%